The prevalence and impact of tension-type headache in school-aged children in Iran - Togha, Mansoureh; Jafari, Elham; Salami, Zhale; Kamali, Koorosh; Mirzaee Godarzee, Hadis; Mirzaee Godarzee, Mohadeseh; Bavarnegin, Sanaz (Frontiers in Neurology, 2023)
Background Tension-Type Headache (TTH) is regarded as the third most prevalent disorder worldwide, prompting children to seek medical attention. Our objective is to investigate the prevalence of TTH among students aged 6 to 18 years in various geographical regions of Iran, while also assessing the impact of headaches on their quality of life. Methods Employing a cross-sectional survey, we have carefully distributed self-completed structured questionnaires to students in 121 meticulously selected schools throughout the country, ensuring the representation of its diverse population. Results Among the 2,958 potential participants, we have included a total of 2031 individuals in our study. This comprises 57.3% children and 42.7% adolescents, with 50.02% being males and 49.97% females. Specifically, we have examined 950 subjects with TTH and 1,081 individuals without any form of headache. TTH was diagnosed in 32.1% of the participants. Notably, we have observed a significant difference in the average age between the TTH subjects and those without headaches. Participants without headaches were more likely to be enrolled in primary schools, while those diagnosed with TTH predominantly attended high schools. We found no significant relationship between urban–rural areas or different geographic regions and the prevalence of TTH or its subtypes. Phonophobia was commonly associated with TTHs. Lastly, the mean quality-of-life score was highest for individuals without headaches, followed by those with low frequency episodic TTH, high frequency episodic TTH, and chronic TTHs. There was also a significant relation between headache severity and quality of life scores. Conclusion The significant prevalence of TTH in children and adolescents and its adverse impact on the daily activities of individuals underscore the utmost importance of accurate diagnosis and efficient management.